Numerical Study of Reconfigurable Mid‐IR Single Photon Sources Based on Functional Ferroelectrics. Issue 3 (29th January 2020) - Kundys, Dmytro; Graffitti, Francesco; McCracken, Richard A.; Fedrizzi, Alessandro; Kundys, Bohdan
Abstract: The future of quantum photonic technology depends on the realization of efficient sources of single photons, the ideal carriers of quantum information. Parametric downconversion (PDC) is a promising route to create highly coherent, spectrally pure single photons for quantum photonics using versatile group velocity matching (GVM) and tailored nonlinearities. However, the functionality to actively control the poling period of nonlinear crystals used in PDC is currently missing, yet would enable to dynamically modify the wavelength of single photons produced in the PDC process. Herein, a detailed GVM study is presented for functional PMN‐0.38PT material which can be dynamically repolled at ambient conditions with fields as low as 0.4 kV mm −1 . The study reveals phase‐matching conditions for spectrally pure single photon creation at 5–6 µm. Further, a practical approach is proposed for on‐flight wavelength switching of the created single photons. The reported reconfigurable functionality benefits a wide range of emerging quantum‐enhanced applications in the mid‐IR spectral region where the choice of single photon sources is currently limited. Abstract : This paper describes a concept under which quantum light sources can be dynamically reconfigured. Numerical study shows it is possible to obtain both pure single photons and wavelength‐switching operation in the mid‐IR window where single photon sources are limited. The suggested mechanism can benefit quantum‐enhanced applications ranging from imaging and sensing to free‐space quantum communication, and quantum information processing.